Seloko pada acara lamaran masyarakat Melayu Jambi: Tindak tutur Searle - Istiqomah Nurzafira; Bambang Prastio; Asman Asman; Yudi Fahriyan (Universitas Lampung, 2020)
The society of Malay Jambi has an oral tradition in the form of seloko which can be found in the marriage proposal event. Nowadays, the existence of seloko in the midst of the globalization era begins to be threatened and rarely found. This research is one of the way to document and preserve seloko so that it can be inherited to the next generation. This research was a descriptive qualitative research. The type of research conducted was the research of speech act proposed by (Searle, 1979). This research aims to describe the type and the function of speech act. The data in this research was in the form of utterances that had been transcribed. The source of data was obtained from the marriage proposal event that occurred in the city of Jambi, the result indicates that there are four types of speech act used in the marriage proposal event. First, the directive speech act with the function of requesting and suggesting. Second, the commissive speech act with the function of giving promise. Third, the expressive speech act with an apology function. Fourth, the representative speech act with the function of the disclosure statement of the information. Seloko on the marriage proposal event is absolutely very useful and important for the both families since it can be used as the foundation and consideration before marriage. dx.doi.org/10.23960/aksara/v21i2.pp156-168